The jaw apparatus of the Late Cretaceous heteromorph ammonoid Pravitoceras. (29th October 2015) - Tanabe, Kazushige; Tsujino, Yasuyuki; Okuhira, Kosuke; Misaki, Akihiro
Abstract: Well-preserved upper and lower jaws of the aptychus-type found inside the body chambers of two specimens of the heteromorph ammonoid Pravitoceras sigmoidale Yabe, 1902 (Nostoceratidae, Ancyloceratina) are described from the Upper Cretaceous Izumi Group in Southwest Japan. They are similar in overall morphology to those of other nostoceratid and diplomoceratid ammonoids currently known, suggesting the morphological stability of the jaw features among these taxa. The equal size of the upper and lower jaws with beak-like rostral projection suggests that the jaw apparatus of this species might function to bite and cut up prey.